Fresno County Bar Association Law Day Luncheon with U.S. Attorney David Levy at Fresno Hilton Ballroom - Watkins, Howard::::::::: (1988)
Colin Daugherty speaking at lectern; seated Fresno County Bar Association President Herbert Levy, U.S. Attorney David Levy, Lawrence O'Neill, and Sandra Snyder